Vulnerability to climate warming and acclimation capacity of tropical and temperate coastal organisms - Vinagre, Catarina (2019)
Ecological forecasting on the likely impacts of climate warming is crucial at a time when several ecosystems seem to be responding to this environmental threat. Among the most important questions are: which are the most vulnerable organisms to climate warming and where are they? Recently, there has been debate on whether the tropics or temperate zones are more vulnerable to warming. Vulnerability toward higher temperatures will depend on the organisms’ thermal limits and also on their acclimation capacity, which remains largely unknown for most species. The aim of the present work was to estimate (1) the upper thermal limits (Critical Thermal Maximum (CTMax)), (2) the warming tolerance (CTMax – Maximum Habitat Temperature) and (3) the acclimation capacity of tropical and temperate rocky shore organisms. Differences in biological groups (decapod crustaceans vs fish) were investigated and the effect of region (tropical vs temperate) and habitat (intertidal vs subtidal) was tested. Overall, 35 species were tested. For the assessment of the acclimation capacity, tropical-temperate pairs of closely related species of shrimp, crab and fish were selected. Warming tolerance was higher for temperate species than for tropical species and higher for subtidal species than for intertidal species, confirming that species with the highest thermal limits have the lowest warming tolerance. All species tested presented some acclimation capacity (CTMaxTrial − CTMaxControl), with the exception of gobiid fish, which was not observed to acclimate. The tropical species tested showed a lower acclimation capacity than their temperate counterparts. Given that tropical rocky shore organisms are already living very close to their thermal limits and that their acclimation capacity is limited, it is likely that the impacts of global warming will be evident sooner in the tropics than in the temperate zone.